Personal and organizational background of corporate entrepreneurs: new technology-based firm evidence - Badoiu, Georgiana Alexandra (2020)
The role of corporate entrepreneurs as employees who generate value for the company and as drivers of innovation and entrepreneurial initiatives is recognized in the literature on entrepreneurship. The purpose of this study is therefore to determine which personal factors characterize corporate entrepreneurs and to analyze which organizational factors have favored the development of intrapreneurial initiatives among corporate entrepreneurs, in the context of a new technology-based firm. Adopting a qualitative approach, this study presents a case study based on surveys and interviews of corporate entrepreneurs and top executives. The results show that corporate entrepreneurs are characterized by having a strong need to learn and grow, and they do not follow the status quo as their peers do. Projects promoted by corporate entrepreneurs can arise even in a context where managers support entrepreneurial initiatives in a non-proactive way, and despite the lack of time and limited resources to execute such projects. Furthermore, corporate entrepreneurs highlight work autonomy, managerial support and rewards as main factors supporting their initiatives.